2021
DOI: 10.1186/s12884-021-04189-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with skin-to-skin contact (SSC) practice: findings from a population-based cross-sectional survey in 10 selected districts of Bangladesh

Abstract: Background Skin-to-skin contact (SSC) practice improves newborn survival and child development through preventing hypothermia in newborns, improving early initiation of breastfeeding practice, and strengthening mother-child bonding. Despite having numerous benefits, it is one of the least practiced interventions in low and middle-income countries (1 to 74%). In Bangladesh, the prevalence of SSC was 26% in 2014. In this study, we aimed to estimate the prevalence of SSC in the study districts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
(59 reference statements)
3
8
3
Order By: Relevance
“…The other striking finding of this study was that mothers who delivered at health facilities are associated with high odds of SCC practices as compared to their counterparts. The finding is consistent with studies conducted elsewhere [20,28,31,32]. It is a fact that in the health facility, there are trained and skilled health professionals, such that they can support mothers to practice SCC.…”
Section: Discussionsupporting
confidence: 90%
“…The other striking finding of this study was that mothers who delivered at health facilities are associated with high odds of SCC practices as compared to their counterparts. The finding is consistent with studies conducted elsewhere [20,28,31,32]. It is a fact that in the health facility, there are trained and skilled health professionals, such that they can support mothers to practice SCC.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of mother and newborn SSC in Papua New Guinea is 45.2%. This prevalence observed in this study is relatively higher than the prevalence of mother and newborn SSC reported in previous studies in Gambia (35.7%),20 Ethiopia (28.1%),21 Nigeria (12.1%),18 and Bangladesh (28%) 24. Also, another recent study conducted in Southern Ethiopia found the prevalence of mother and newborn SSC to be 35.3% 22.…”
Section: Discussioncontrasting
confidence: 70%
“…This prevalence observed in this study is relatively higher than the prevalence of mother and newborn SSC reported in previous studies in Gambia (35.7%), 20 Ethiopia (28.1%), 21 Nigeria (12.1%), 18 and Bangladesh (28%). 24 Also, another recent study conducted in Southern Ethiopia found the prevalence of mother and Open access newborn SSC to be 35.3%. 22 However, the prevalence observed in our study is lower than the prevalence found in a study conducted in Singapore, which reported SSC to be 84.0%.…”
Section: Discussionmentioning
confidence: 99%
“…This result is higher than a study conducted in Africa that indicated a 1–9% prevalence of SSC [ 26 ]. The finding is also higher than the study done in Bangladeshi 28 % [ 27 ] and Arabian countries 25 % [ 28 ]. The disparity of the results is from the variation in the number of articles incorporated into the analysis.…”
Section: Discussioncontrasting
confidence: 67%